2022
DOI: 10.3390/ijerph19063252
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Mental Health Care of Children and Adolescents in Switzerland: Results of a Survey among Mental Health Care Professionals after One Year of COVID-19

Abstract: Background: To assess the impact of the COVID-19 pandemic on treatment demand and supply in children and adolescents with mental disorders during the first year of the pandemic from the perspective of child and adolescent psychiatrists and psychologists in Switzerland. Methods: The survey was conducted anonymously, in German or French and online in April/May 2021. Mental health professionals working in child and adolescent psychiatry, psychotherapy services or independent practices were contacted by email. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…This probably reflects the fact that usually the more severe, complex, or acute cases are seen and subsequently treated in clinics for child and adolescent psychiatry rather than in independent practice settings. As emergencies dramatically increased during the corona crisis in Switzerland among children and adolescents with mental health problems (Berger et al 2022 ; Werling et al 2022b ), along with a shortage of treatment places and longer waiting time before admission to treatment, many mental health professionals working in independent practice must have been confronted with severe cases, which in normal times would rather have been treated in clinics for child and adolescent psychiatry. This was also reported in the free text sections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This probably reflects the fact that usually the more severe, complex, or acute cases are seen and subsequently treated in clinics for child and adolescent psychiatry rather than in independent practice settings. As emergencies dramatically increased during the corona crisis in Switzerland among children and adolescents with mental health problems (Berger et al 2022 ; Werling et al 2022b ), along with a shortage of treatment places and longer waiting time before admission to treatment, many mental health professionals working in independent practice must have been confronted with severe cases, which in normal times would rather have been treated in clinics for child and adolescent psychiatry. This was also reported in the free text sections.…”
Section: Discussionmentioning
confidence: 99%
“…A small group of health professionals with no published email address was contacted by letter, which included a QR code leading to the online survey. This survey for mental health professionals was developed as a complement and follow-up to surveys for patients and their parents on the impact of the pandemic conducted by the authors (Werling et al 2021a , b ; Werling et al 2022a , b ). The online survey was available in German and French, which are the two most frequently spoken languages in Switzerland (main languages for approximately 85% of inhabitants).…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Research that dealt with young people, as a particularly sensitive group, from the beginning of the COVID-19 pandemic until today, have produced a lot of information about significantly lower health-related quality of life (HRQoL), damaged relationships with friends and reduced social contacts, increased number of arguments within families, difficulties with online learning and keeping up with classes, which are all triggers for mental health problems. Many of them studied the occurrence of emotional symptoms, behavioral problems, hyperactivity and problems with peers, as well as self-reported anxiety, depressive symptoms and psychosomatic complaints, such as headaches, stomach aches, feeling low or sleeping problems [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“… 9 On the other hand, child and adolescent mental health professionals reported that their workload increased and patient treatment was delayed compared to the pre-pandemic period. 10 Therefore, while the COVID-19 pandemic triggered the emergence of new psychological struggles, it also limited access to treatment for vulnerable populations who already had mental health problems. 11 …”
Section: Introductionmentioning
confidence: 99%